Research on the impact of tech founders on enterprise innovation and market performance - XU, Zhihao (Institutional Knowledge at Singapore Management University, 2024)
In recent years, increased entrepreneurial projects have been spearheaded by scientists and technical experts. The likelihood of success for such entrepreneurship has garnered considerable attention. Leveraging theories including upper echelons theory and attention-based view, this study develops an analytical framework, research hypotheses, and measurement models to examine the correlation between entrepreneurs’ technical backgrounds and enterprise performance. Use first-hand and second-hand data together constitute the core data sources. Utilizing a fixed effect regression analysis model, the study elucidates the correlation between the technical backgrounds of entrepreneurs and enterprise performance. Building upon empirical research, this study also selects entrepreneur cases of typical significance. It conducts an in-depth analysis and comparison of the impact pathways and mechanisms of the founder’s technical background on enterprise performance from several dimensions including the founder’s professional and technical experience, entrepreneurial experiences, business operations, and enterprise performance. The study obtains three main conclusions: (1) There are significant differences in how entrepreneurs’ technical backgrounds influence enterprise performance across various lifecycle stages. Specifically, entrepreneurs’ technical backgrounds significantly impact enterprise innovation performance, showing a negative impact on enterprises in the development and growth stages. Entrepreneurs’ technical backgrounds significantly impact enterprises’ market performance, showing a negative impact on enterprises in the development and growth stages. (2) Tech founders impact enterprise performance in the early stage through two mechanisms. First, their professional and technical experiences shape their personalities and behaviors affecting enterprise performance. Second, entrepreneurs typically wield considerable control rights in startup and growth enterprises, greatly influencing business strategy and subsequently enterprise performance. The combination of these two mechanisms often amplifies management weaknesses inherent in tech founders, significantly impacting enterprise operations negatively. (3) Scientific and technological (sci-tech) enterprises should focus on balancing technological innovation with commercialization and enhance enterprises’ sustainable innovation abilities.